Automatic Capacitor Bank Planning Design using Microcontroller for Power Factor Optimization - Ibrohim, Ibrohim; Haryudo, Subuh Isnur; Endryansyah, Endryansyah; Zen, Hafidz Nindhom (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2026)
Low power factor (cos φ) remains a prevalent issue in residential electrical installations, primarily due to inductive appliances such as air conditioners, refrigerators, and water pumps, which increase reactive power and reduce overall system efficiency. This condition leads to voltage drops, increased current flow, and higher I²R losses, affecting electricity expenditure and long-term equipment reliability. To address this problem, this study proposes an automatic power factor correction system based on reactive power compensation, where capacitors function as local suppliers of reactive power to stabilize voltage and reduce grid loading. The system utilizes an Arduino Nano microcontroller integrated with a PZEM-004T sensor for real-time monitoring of voltage, current, and power factor. Based on the measured parameters, capacitor switching is performed using relay-based control to enable adaptive compensation according to load variations. Experimental testing was conducted under real household operating conditions for a total duration of four months, including pre- and post-intervention measurements. The results showed a substantial improvement in power factor, increasing from 0.79–0.82 to 0.91–0.99 after capacitor bank installation. Current consumption also decreased—for example, from 4.23 A to 3.50 A in Week 1 and from 9.61 A to 8.10 A in Week 5, indicating reduced power losses and improved voltage stability. Furthermore, energy usage declined from 737 kWh to 605 kWh over two months, resulting in an energy saving of 17.9%. In conclusion, the proposed system demonstrates that low-cost automated power factor correction can effectively enhance residential energy efficiency and offer measurable economic benefits for household consumers.